Hydrogen pressure dependent in-situ electrical studies on Pd/C nano-composite. (2nd February 2017) - Kulriya, P.K.; Kumar, Mohit; Singh, Jitendra; Avasthi, D.K.
Abstract: In present study, the effect of hydrogen gas pressure on the electrical characteristics of the Pd nanoparticle embedded in the carbon matrix was investigated. The structural characterizations of the as-prepared samples were performed using synchrotron radiation x-ray diffraction (SR-XRD), and transmission electron microscopy (TEM). In-situ electrical transport studies for high concentration sample showed a slow response time (∼30 s) and the resistance versus time curves have similar behavior that of Pd thin films, whereas the lower concentration sample has a fast response time (5 s) along with peculiar response curve. The pressure dependent studies showed that spillover effect was dominant, when samples were exposed to hydrogen gas at low pressure. The superior sensing performance of the lower concentration sample was observed due to extraordinary high surface to volume ratio of nanoparticles as well as good separation provided by the carbon matrix. The spillover effect based hydrogen absorption–desorption mechanism proposed in the present study is important for understanding the hydrogen absorption in the metal nano-composite system and its application in the design of advanced materials for hydrogen gas sensors. Highlights: Synthesis and characterization of Palladium nanoparticle in the carbon matrix. Effect of hydrogen pressure on the spillover of H in Pd/C film is investigated. Slow response time (∼30 s) observed for high concentration sample. Fast response time (5 s) observed for lower concentration sample.